IMPLEMENTASI PENDEKATAN BACKWARD DESIGN DALAM MENDUKUNG KETERCAPAIAN TUJUAN PEMBELAJARAN PADA FASE A SEKOLAH DASAR - Asriningrum, Novita; Nurfidia, Alifha; Maulina, Eva; Alfiyah, Vivi; Sutarni, Sri; Ghufron, Anik (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the implementation of the Backward Design approach in supporting the achievement of learning objectives in Phase A of elementary school. The study employed a qualitative approach with a case study design in lower-grade classrooms. Data were colle cted through observations, semi-structured interviews, analysis of instructional documents, student work, and teachers’ reflective journals. Data were analyzed using the Miles, Huberman, and Saldaña model, including data condensation, data display, and conclusion drawing and verification. Data credibility was ensured through source and technique triangulation. The findings show that Backward Design helped establish alignment among learning objectives, assessments, and learning activities. Teachers became more focused in planning and implementing instruction, while students demonstrated active engagement, improved ability to follow structured instructions, and greater independence in completing tasks. However, its implementation required more planning time and teachers’ ability to appropriately design assessments suited to the developmental characteristics of Phase A students.